Analysis of Raw Material Supply in Sadamalun Caramel Potato Donut Msmes in Karawang - Kristianto, Bima Setyo Aji; Oktavia, Dewi; Apriani, Winda; Suherman, Ujang (MultiTech Publisher, 2024)
This study aims to determine the most effective inventory management at UMKM Caramel Potato Donut Sadamalun Karawang. Using a descriptive qualitative approach, researchers analyzed inventory management in the UMKM Caramel Potato Donut Sadamalun Karawang. Data from observations, interviews and documentation shows that inventory management at UMKM Caramel Potato Donut Sadamalun Karawang is not optimal. This is indicated by the minimal inventory available and high storage costs and also high inventory costs, due to limitations in managing inventory. For this reason, researchers use the EOQ technique to analyze inventory which can support inventory management effectively and efficiently